Effects of School Shooting on School Climate: A Review of Social Bond Theory - Erbay, Ayhan; Ildırım, Ezgi (The Bulletin of Legal Medicine, 2021)
Although school shooting is among the primary problems of society from time to time, it is in reality an issue that society pays attention to when such an event breaks out. School shooting, on the other hand, has a devastating impact on students, teachers, and other school staff, as well as deeply shaking the school climate. At this point, Social Bond Theory has been used as a theoretical framework to understand the effects of the school shooting. The theory proposes that when school shooting occurs especially students de-attach from school, therefore from the society. They do not commit to social norms and rules, and eventually, lose their faith in society because of their school shooting. In this study, it was discussed how the school shootings effect the school climate, and some prevention suggestions were developed.
Keywords: school shooting; Social bond theory; school climate